2018
DOI: 10.1108/ijem-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of MBA: on the role of network effects in influencing the selection of elective courses

Abstract: Purpose The purpose of this paper is to outline the importance of social network effects in influencing the elective (courses) selection among masters of business administration (MBA) students and its role in influencing the efficacy of MBA. As such, given the enormous time and investment required for students to pursue an MBA and the role of electives in forming the student’s knowledge base, it is important to consider the decision process of students while selecting elective courses as they pursue their degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Researchers tried to identify the antecedents of actual learning processes in educational programs (Garger et al , 2010; Eom et al , 2006) and they mainly focused on participants’ personal and social characteristics as the antecedents of learning effectiveness (El Massah and Fadly, 2017). Among the individuals’ characteristics, researchers discussed the role of individual absorptive capacity (Rezaei-Zadeh and Darwish, 2016), knowledge sourcing initiative (Gray and Meister, 2004) and learning orientation (Kang et al , 2018), while among students’ social characteristics that impact on the effectiveness of learning earlier research identified the network ties (Roy and Parsad, 2018), the shared understandings (Alavi and Tiwana, 2002) and the pro-sharing norms (Kankanhalli et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers tried to identify the antecedents of actual learning processes in educational programs (Garger et al , 2010; Eom et al , 2006) and they mainly focused on participants’ personal and social characteristics as the antecedents of learning effectiveness (El Massah and Fadly, 2017). Among the individuals’ characteristics, researchers discussed the role of individual absorptive capacity (Rezaei-Zadeh and Darwish, 2016), knowledge sourcing initiative (Gray and Meister, 2004) and learning orientation (Kang et al , 2018), while among students’ social characteristics that impact on the effectiveness of learning earlier research identified the network ties (Roy and Parsad, 2018), the shared understandings (Alavi and Tiwana, 2002) and the pro-sharing norms (Kankanhalli et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Executive education programs reflect early to mid-career executives who are looking to fulfill their personal needs by seeking higher education versus any financial imperative. Apart from this, executive education also serves to fulfill the individuals' self-esteem needs as identified in Maslow's Pyramid as well (Roy & Parsad, 2018).…”
Section: Discussionmentioning
confidence: 99%